Structural Identification of Impurities in Pioglitazone Hydrochloride Preparations by 2D-UHPLC-Q-Exactive Orbitrap HRMS and Their Toxicity Prediction - Dandan Zhang; Weijian Wang; Haiyun Zhao; Song Wang; Mingyan Yu; Dongmei Zhang; Wenkun Liu; Qiangsheng Xie; Dejun Chen (International Journal of Analytical Chemistry)
Pharmaceutical companies and regulatory agencies have more and more concerns for impurities in pharmaceuticals and their toxicity. In this work, heart-cutting two-dimensional ultrahigh-performance liquid chromatography (2D-UHPLC) in combination with high-resolution mass spectrometry (HRMS) was used, setting HRMS as positive mode of electrospray ionization to identify five impurities in pioglitazone hydrochloride preparations. With the heart-cutting 2D-UHPLC and online desalting technique, the structures of five impurities were deduced in an analysis of MSn data. And three of them, Impurity-2, Impurity-3, and Impurity-5, have never been reported before. The fragmentation patterns of five impurities were proposed on a basis of accurate mass and fragment ions in this study. Since the toxicity of impurities is relevant to their structures, toxicology of all five impurities was predicted by three software tools, and the result showed that these compounds have good safety profile.